Interlocking brick IBS / Arif Khairin Rosli - Rosli, Arif Khairin (2021)
IBS Interlocking Brick one of the alternative design and construction type that we can have now in Malaysia with take the nature and green house concept the building end develop based on all Al Ansar IBS PLT construction project. This report was conducted for all contractor that use Interlocking Brick that Al Ansar IBS already has been using it for the past year. The objective of this report is to show the Interlocking Brick and how far it fulfills the requirements in the guideline. With use a loadbearing wall design we will change the old conversional type of construction with advantages that this IBS Interlocking Brick can offer to us. The most important consequences of this report is to compile all about Interlocking Brick type and how to build a house that Al Ansar PLT already use for a year in a each project that this company already run.